The intergenerational welfare state - Andersen, Torben; Bhattacharya, Joydeep (Munich, 2013)
"The welfare state is not merely a stand-in for missing markets; it can do a whole lot more. When generations overlap and the young must borrow to make educational investments, a dynamically-efficient welfare state, by taxing the middle-aged and offering a compensatory old-age pension, can generate higher long-run human capital and welfare compared to laissez faire. Along the transition, no generation is hurt and some are better off. If an intergenerational human capital externality is present, unfunded pensions can be gradually phased out entirely. Public pension reform can be rationalized on efficiency grounds without relying on political-economy concerns or aging."